The interaction of occupational stress, mental health, and cytokine levels on sleep in Xinjiang oil workers: A cross-sectional study - Li, Xue; Xue, Qiaoyun; Yi, Xiaoting; Liu, Jiwen (Frontiers in Psychiatry, 2022)
Background: Sleep occupies one third of a person's life, and good sleep quality is an important factor to ensure good health. Methods: In this study, stratified cluster random sampling was used to conduct a cross-sectional survey on the occupational stress, mental health and sleep quality of 1141 oil workers in Xinjiang from June 2019 to January 2020, and 30% of the participants were randomly selected for measurement of their cytokine levels Interleukin 2(IL-2)、Interleukin 6(IL-6)、Interleukin 8(IL-8)、Tumor necrosis factor α(TNF-α). The objectives were to analyze the effects of occupational stress and mental health on sleep quality, and to explore the effects of occupational stress, mental disorders and cytokine interactions on sleep. Results: There are 646 individuals (56.6%) suffered from sleep disorders; the incidence of sleep disorders differed according to sex, age, professional title, working years, type of work and shift (P<0.05). The scores for occupational stress, mental health and sleep quality were positively correlated (P<0.05). Multivariate logistic regression analysis showed that age (30–45 years) (OR=1.753, 95%CI:1.067–2.881) ), junior College and above (OR=1.473, 95%CI:1.025–2.118), borehole operation (OR=2.689, 95%CI:1.508–4.792), extract oil (OR=2.405, 95%CI:1.229–4.705), drilling (OR=1.791, 95%CI:1.017–3.155), shift work (OR=2.144, 95%CI:1.615–2.846), occupational stress (OR=1.007, 95%CI:1.002–1.013), and mental disorders (OR=1.020, 95%CI:1.009–1.032) ) are risk factors for sleep disorders. The high occupational stress group and the mental disorders group as the control group, the results showed that the interaction between IL-2 and moderate occupational stress (OR=0.778, 95%CI:0.778–0.942) 、 IL-2 and non-mental disorders (OR=0.398, 95%CI:0.398–0.468) were protective factors for the occurrence of sleep disorders . Conclusion: Oil workers have serious sleep problems, so effective measures should be taken to reduce occupational stress and relieve mental health problems, and cytokine levels can be used as a predictor of sleep disorders.